2002
DOI: 10.1046/j.1460-9568.2002.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

A divergent gene family encoding candidate olfactory receptors of the moth Heliothis virescens

Abstract: The antennae of moths have been an invaluable model for studying the principles of odour perception. In spite of the enormous progress in understanding olfaction on the molecular level, for the moth one of the key elements in olfactory signalling, the odourant receptors, are still elusive. We have assessed a genome database of a heliothine moth (Heliothis virescens, Noctuidae) and employed exon-specific probes to screen an antennal cDNA library of this species. Analysis of isolated cDNA-clones led to the disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
184
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(193 citation statements)
references
References 35 publications
8
184
0
1
Order By: Relevance
“…Data mining of a partial genomic database from H. virescens in combination with cDNA-library screening (12) led to the identification of numerous cDNA clones containing long ORFs. BLAST comparisons of the sequences to entries in the EMBL͞GenBank and SwissProt databases revealed that several of the newly isolated cDNAs appear to be related to some of the candidate olfactory receptors from Heliothis (12), Drosophila (4-8), or Anopheles (9-11), thus suggesting that the isolated cDNA clones encode novel members of the olfactory receptor family.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data mining of a partial genomic database from H. virescens in combination with cDNA-library screening (12) led to the identification of numerous cDNA clones containing long ORFs. BLAST comparisons of the sequences to entries in the EMBL͞GenBank and SwissProt databases revealed that several of the newly isolated cDNAs appear to be related to some of the candidate olfactory receptors from Heliothis (12), Drosophila (4-8), or Anopheles (9-11), thus suggesting that the isolated cDNA clones encode novel members of the olfactory receptor family.…”
Section: Resultsmentioning
confidence: 99%
“…To find new genes encoding candidate chemoreceptors, we extended the strategy that was used successfully to detect the first candidate olfactory receptors in H. virescens (12) by using the sequences of Heliothis receptor 1-9 (HR1-HR9) and of newly identified HRs, as well as the sequences of candidate olfactory receptors from Drosophila melanogaster (4)(5)(6)(7)(8) and Anopheles gambiae (9)(10)(11) in BLAST analyses (22,23) of the nonpublic Heliothis genomic database.…”
Section: Materials and Methods Animals And Tissue Preparation H Virmentioning
confidence: 99%
See 3 more Smart Citations